An Analytic Contemplation of the Conspicuous Vicissitudes in the Histomorphology of Corpuscles of Stannius of a Freshwater Catfish Mystus tengara (Hamilton, 1822) due to the Exposure of ZnS Nanoparticles. (29th November 2015) - Chatterjee, Nilanjana; Bhattacharjee, Baibaswata
Abstract : Enhanced surface photooxidation property associated with the ZnS nanoparticles caused the reduction of dissolved oxygen content in water in a dose dependent manner, when ZnS nanoparticles of different sizes are exposed to the water in various concentrations. This property was more prominent for ZnS nanoparticles with smaller sizes. Mystus tengara, exposed to ZnS nanoparticles, responded to hypoxia with varied behavioural, physiological, and cellular responses in order to maintain homeostasis and organ function in an oxygen-depleted environment. The histomorphology of corpuscles of Stannius of the fish showed conspicuous vicissitudes under exposure of ZnS nanoparticles. The population of the cell type with granular cytoplasm showed significant increase at the expense of the other that consisted of agranular cytoplasm with increasing nanoparticle concentration. This can be explained as the defence mechanism of the fish against ZnS nanoparticle induced hypoxia and environmental acidification. The altering histomorphology has been studied employing an analytical approach.